Recent update on cerebral sparganosis: A bibliometric analysis and scientific mapping - Dirgahayu, Paramasari; Ilyas, Muhana F.; Rahma, Annisa A.; Hanifa, Shafira N.; Wijayanto, Matthew A.; Triniputri, Winastari Y.; Lukas, Graciella A.; Wiyono, Nanang; Sari, Yulia; Mashuri, Yusuf A. (Narra J, 2024)
Human sparganosis, a parasitic infection prevalent in Asia, can progress to cerebral sparganosis, a severe condition with significant neurological symptoms. Diagnosis and treatment are challenging due to its clinical similarity to other infections, highlighting the need for improved detection and management strategies. The aim of this study was to observe research trends, key contributors, gaps in the existing knowledge, diagnosis challenges, effective treatment options, and prevention strategies, providing recommendations for future research directions and clinical practice improvements on cerebral sparganosis. A bibliometric analysis was conducted by extracting 139 documents from the Scopus database in June 2024. The retrieved data were analyzed using the R package's Bibliometrix (Biblioshiny) and VOSviewer. Spanning 97 different sources, the research exhibited an annual growth rate of 2.5%. Annual scientific production revealed fluctuating research activity with peaks in 2010 and 2011 and notable citation peaks in 1996 and 2005, indicating pivotal studies that significantly influenced subsequent research. Early studies focused on diagnosis and specific parasites, while recent studies (2010–2024) have increasingly addressed clinical outcomes, treatment strategies, and advanced diagnostic techniques. Trends revealed a shift towards clinical and diagnostic advancements, with recent emphasis on diagnostic imaging, immunoassays, and the relationship between cerebral sparganosis and brain tumors. In conclusion, the studies on cerebral sparganosis underscore the potential for enhancing clinical practice by improving diagnostic accuracy, informing treatment decisions, and implementing targeted screening efforts based on epidemiology and risk factors. Recommendation to further study needs to notify the cerebral sparganosis in high-risk countries with similar socioeconomic and cultural characteristics to endemic regions, including Indonesia.